Herramientas de economía ecológica para la evaluación de la sostenibilidad de biomasas (2020)
This study applied some of the tools of ecological economics to assess the sustainability of the main biomasses in Cienfuegos province, Cuba. For this purpose, the following were selected as the main biomasses: bagasse; cachaza or press cake, as a by-product of the sugarcane juice clarification process, Agricultural Harvest Waste (AHR), rice husks and forest residues. The quantities available were determined through the survey in each production unit, in order to estimate the total energy, as well as the reduction of CO2released into the atmosphere for each biomass source. Finally, the Analytical Hierarchy Process(AHP) was applied as a multi-criteria decision technique to evaluate the sustainability of the biomass alternatives presented. In addition, a sensitivity analysis was carried out, due to the subjectivity of this decision technique.